Manuel Zimmermann, Economic Efficiency and the Division of Large Procurement Contracts Into Lots: An Analysis 2, - Różowicz, Konrad (Studia Prawa Publicznego, 2018)
Manuel Zimmermann, Economic Efficiency and the Division of Large Procurement Contracts Into Lots: An Analysis (Analiza efektywności ekonomicznej podziału zamówień na części), „European Procurement & Public Private Partnership Law Review” 2017, vol. 12,